2020
DOI: 10.1002/ajmg.a.61535
|View full text |Cite
|
Sign up to set email alerts
|

An ACVRL1 gene mutation presenting as vein of Galen malformation at prenatal diagnosis

Abstract: Hereditary hemorrhagic telangiectasia (HHT) is a rare autosomal dominant disease.The diagnostic criteria of HHT, or Curaçao criteria, include the following: recurrent epistaxis or nighttime nose bleeding, mucocutaneous telangiectases, visceral arteriovenous malformation, or an appropriate family history. The diagnosis is classified as definite if three criteria are present, possible if two criteria are present, and unlikely if only one is present. Nowadays, the confirmation of HHT diagnosis is based on molecul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…These are usually small, superficial, multiple, and asymptomatic and ascertained primarily in adults either incidentally or due to headache or bleed [Bokhari and Bokhari, 2021]. Rare instances of large bAVMs including VGM have been reported in the literature presenting in the fetal or neonatal period [Tsutsumi et al, 2011;Chida et al, 2013;De Luca et al, 2020]. More than 600 different mutations have been found in ENG or ACVRL1 in HHT families.…”
Section: Discussionmentioning
confidence: 99%
“…These are usually small, superficial, multiple, and asymptomatic and ascertained primarily in adults either incidentally or due to headache or bleed [Bokhari and Bokhari, 2021]. Rare instances of large bAVMs including VGM have been reported in the literature presenting in the fetal or neonatal period [Tsutsumi et al, 2011;Chida et al, 2013;De Luca et al, 2020]. More than 600 different mutations have been found in ENG or ACVRL1 in HHT families.…”
Section: Discussionmentioning
confidence: 99%
“…The improvement of methods to detect prenatal malformations led to the diagnosis of HHT even in utero, although only in exceptional cases; Saleh et al [ 48 ] reported the diagnosis of liver AVM with fetal magnetic resonance imaging (MRI), following ultrasound (US) evidence of cardiomegaly at 32 weeks of pregnancy, and De Luca et al [ 49 ] reported on the presence of a huge malformation of the vein of Galen associated with ventriculomegaly detected with US at 26 weeks, then confirmed with MRI.…”
Section: Arterovenous Malformations (Avm)mentioning
confidence: 99%
“…In the aftermath of US/MRI diagnosis in both patients, molecular evidence was obtained for mutations in ENG and ACVRL1 respectively. It is regrettable to note that in both cases, familial evidence for HHT was already available [ 49 ] or could have been easily obtained [ 48 ] following the Curaçao criteria, but this evidence did not prompt any genetic counselling about the disease in general, nor any advice to the families about the possibility of observing complications of the disease even in children.…”
Section: Arterovenous Malformations (Avm)mentioning
confidence: 99%
See 1 more Smart Citation
“…These malformations are largely sporadic, possibly due to an early insult such as somatic mutations [ 31 ]. However, recent studies reported that some of the VGAMs were associated with germline mutations in RASA1 and EPHB4 , and ACVRL1 genes [ 33 34 35 ].…”
Section: Composition Of An Rnvd Panel and Prevalence Of Each Disease In Koreamentioning
confidence: 99%